The Molecular Recognition of Lurasidone by Human Serum Albumin: A Combined Experimental and Computational Approach - Nevena Živković; Emina Mrkalić; Ratomir Jelić; Jovica Tomović; Jadranka Odović; Marina Ćendić Serafinović; Miroslav Sovrlić (Molecules)
Lurasidone (LUR) is an antipsychotic drug whose interaction with human serum albumin (HSA) plays a crucial role in its pharmacokinetic and pharmacodynamic properties. A thorough understanding of LUR’s binding mechanism to HSA is crucial for predicting its transport, distribution, and potential drug interactions. Methods: The interaction between LUR and HSA was investigated using fluorescence and circular dichroism (CD) spectroscopy, followed by molecular docking simulations. Binding characteristics were analyzed through quenching mechanisms, thermodynamic parameters, and competitive site marker experiments. Results: This study revealed a systematic decrease in HSA fluorescence intensity with increasing LUR concentration, indicating a static quenching mechanism driven by non-fluorescent complex formation. Binding constants suggest enhanced complex stability at higher temperatures, with thermodynamic analysis confirming an endothermic, hydrophobic interaction. Competitive site marker assays and synchronous fluorescence spectra confirmed that LUR primarily binds to site I (subdomain IIA) near tryptophan residues. Conformational changes in HSA, observed as a decrease in α-helix content, further demonstrate the structural impact of LUR binding. Conclusions: These findings offer key insights into the molecular interactions between LUR and HSA, enhancing our understanding of LUR’s pharmacokinetics and its potential interactions with other drugs. Understanding these binding characteristics can aid in optimizing LUR’s clinical application and predicting possible interactions with other biomolecules.